Role of progression of training volume on intramuscular adaptations in patients with chronic obstructive pulmonary disease - Nyberg, Andre; Milad, Nadia; Martin, Mickael; Patoine, Dany; Morissette, Mathieu C; Saey, Didier; Maltais, François (Frontiers in Physiology, 2022)
Introduction: Quadriceps dysfunction is a common systemic manifestation of chronic obstructive pulmonary disease (COPD), for which treatment using resistance training is highly recommended. Even though training volume is suggested to be a key explanatory factor for intramuscular adaptation to resistance training in healthy older adults, knowledge is scarce on the role of progression of training volume for intramuscular adaptations in COPD. Methods: This study was a sub-analysis of a parallel-group randomized controlled trial. Thirteen patients with severe to very severe COPD (median 66 yrs, forced expiratory volume in 1 s 44% predicted) performed 8 weeks of low-load resistance training. In a post hoc analysis, they were divided into two groups according to their training volume progression. Those in whom training volume continued to increase after the first 4 weeks of training outlined the continued progression group (n = 9), while those with limited increase (<5%) or even reduction in training volume after the initial 4 weeks composed the discontinued progression group (n = 4). Fiber-type distribution and oxidative muscle protein levels, i.e., citrate synthase (CS), hydroxyacyl-coenzyme A dehydrogenase (HADH), mitochondrial transcription factor A (TfAM) as well as quadriceps endurance measures (total work from elastic band and isokinetic knee extension tests), were assessed before and after the intervention period. Results: The continued progression group sustained their training volume progression during weeks 5–8 compared to weeks 1–4 (median +25%), while the discontinued progression group did not (median -2%) (p = 0.007 between groups). Compared with baseline values, significant between-group differences in fiber type distribution and TfAM muscle protein levels (range ± 17–62%, p < 0.05) and in individual responses to change in Type I and Type IIa fiber type proportion, CS, HADH, and TfAM muscle protein levels outcomes (median 89 vs. 50%, p = 0.001) were seen in favor of the continued progression group. Moreover, only the continued progression group had a significant increase in HADH muscle protein levels (+24%, p = 0.004), elastic band (+56%, p = 0.004) and isokinetic (+7%, p = 0.004) quadriceps endurance, but the between-group differences did not reach statistical significance (range 14–29%, p = 0.330–1.000). Discussion: The novel findings of the current study were that patients with COPD who had a continued progression of training volume across the 8-weeks intervention had an increased proportion of Type I fibers, and TfAM muscle protein levels and decreased proportion of Type II fibers compared to those that did not continue to progress their training volume after the initial weeks. Additionally, HADH muscle protein levels and quadriceps endurance measurements only improved in the continued progression group, although no significant between-group differences were seen. These findings highlight the importance of continued progression of training volume during resistive training to counteract quadriceps dysfunction within the COPD population. Still, considering the small sample size and the post hoc nature of our analyses, these results should be interpreted cautiously, and further research is necessary.